Inter-District Disparities in Health Facilities in Karnataka - Rajeshwari, U R; Emmanual, P J (International Research Journal of Management, IT & Social Sciences, 2014)
Social media refers to the online media that allows multi-directional conversations and real time interactions such as social networking sites (SNS), blogs, discussions forums, content sharing, social bookmarks, wikis etc. Over the last decade, social media marketing has become a key focus area for both marketing practitioners and researchers. This paper focuses on the impact of social media in the domain of social marketing.For this study, we consider previous academic research in the area of social media and social marketing published in eminent research journals and management. After creating a summative background of social media and social marketing, we propose a model to understand the role of social media as a catalyst in the process of social change. Finally, we present two cases where social media played a significant role as a social catalyst.Â